The Influence of Motivation, Training and Compensation on Employee Performance - Awoitau, Ruth; Noch, Muh Yamin; Khotimah, Khusnul (Yayasan Pendidikan Bukhari Dwi Muslim, 2024)
Purpose: This study examines the impact of motivation, training, and compensation on employee performance at the Secretariat of the DPRD of Jayapura Regency. Research Design and Methodology: The research employs a quantitative approach, utilizing surveys and statistical analysis to evaluate the effects of motivation, training, and compensation on employee performance. Data was collected from employees at the Secretariat of the DPRD of Jayapura Regency and analyzed using simultaneous testing methods to determine the significance of each variable. Findings and Discussion: The results indicate that motivation, training, and compensation significantly influence employee performance individually and collectively. These findings highlight the potential for significant improvement in employee performance. Motivation enhances performance by fostering a positive work environment and employee engagement. Training improves performance by developing employee skills and competencies. Compensation boosts performance by providing financial and non-financial rewards that increase employee satisfaction and motivation. These findings underscore the critical role of these factors in organizational success and provide a hopeful outlook for the future. Implications: This study underscores the importance of a comprehensive approach to enhancing employee performance through motivation, training, and compensation. To create a motivated and productive workforce, organizational leaders and managers should focus on supportive leadership, continuous skill development, and fair compensation policies. These strategies can foster a conducive work environment, driving organizational success. Future research should explore these factors in diverse contexts and over extended periods to validate and expand upon these findings.